Valorisasi Biji Labu Pada Produk Pangan dan Potensinya Sebagai Makanan Fungsional: Kajian Literatur - Herni Purwantari (International Forum of Researchers and Lecturers, 2026)
Pumpkin seeds (Cucurbita spp.) are a byproduct of pumpkin that has great potential to be developed as a functional food ingredient due to their high nutritional content and bioactive compounds. This article aims to examine the valorization (utilization) of pumpkin seeds in various food products and their potential as a functional food. The method used was a narrative literature review through a search of the Google Scholar, ScienceDirect, PubMed, and MDPI databases for the period 2016–2026. The results of the study indicate that pumpkin seeds have been applied in various food products such as cookies, crackers, bread, biscuits, cakes, muffins, and snack bars. The addition of pumpkin seeds generally increases the content of protein, fiber, unsaturated fatty acids, minerals, and bioactive compounds that contribute to antioxidant activity. However, increasing the proportion of pumpkin seeds also affects the physical and sensory characteristics of the product, such as darker color, decreased volume, and changes in texture due to reduced gluten content in the dough. Therefore, formulation optimization is needed to achieve a balance between increasing nutritional value and consumer acceptance. Overall, pumpkin seeds have the potential to be used as an ingredient in the development of functional foods.